The Effect of Digital Era on Human Visual Working Memory - Dandan Tang; Jiangtao Chen; Ping Xu (Brain and Behavior)
ABSTRACT Background The digital age has had a profound impact on our lives and cognitive abilities, such as working memory. Typically, visual working memory (VWM) is an important aspect of our working memory. As a crucial cognitive function for individuals, VWM has been extensively studied in the context of the digital age and may be affected by the digital age. Objective This review aims to provide a summary of the impact of the digital age on VWM and cover various aspects and novel methods for investigating its effects on our VWM. Methods Qualitative review of the VWM in the context of the digital age. Results This paper reviews the research on VWM in the context of the digital era, expounds the influence of both the digital content usage and the active video games on the VWM, introduces the application of the virtual technology in the research of VWM, and puts forward the future research direction of VWM in the context of the digital era. Conclusion By synthesizing the existing research, this review sheds light on the complex relationship between the digital age and VWM, as well as identifies potential avenues for future research on VWM.